(untitled) (Journal of Universal Excellence, 2026)
Research question (RQ): What is the prevalence rate of urinary incontinence (UI) among top sports female athletes and in the control group? Purpose: The aim of the study was to determine the prevalence rate of urinary incontinence among top sports female athletes and volunteers from the general public of the same age group.. Method: The sample consisted of 176 female athletes from the sports clubs registered at the Sports Association Ljubljana, aged 15 – 25 years. All the participants were nulliparas. The method of primary data collection was used to collect data using a questionnaire as a research instrument. The differences among averages were tested with variance analysis and the statistical significance level was set at p≤ 0.05. Results: A total of 300 questionnaires, completed by 150 athletes and 150 volunteers were analysed. A statistically significant difference among the two groups was established in regards to their height and weight. The athletes competed in nine different sports 11±3,3 hours per week. Involuntary release of urine was reported by 20% of athletes and 11.4% of volunteers from the control group. The difference between the groups was not statistically significant. Organisation: The study urges a claim for greater awareness of the sports milieu of the pelvic floor problems and urinary incontinence along with the necessary measures to help female athletes recognise the first symptoms of urinary incontinence. The coaches and the athletes should be informed of the necessity of pelvic muscles exercises which should become a constituent part of every training session. Society: Urinary incontinence presents the greatest financial burden among all urological disorders. The financial burden of disease related to urinary incontinence includes direct expenses (diagnosis, treatment, hygiene, daily care) and the consequences of the disease (treatment of fractures due a slip or fall accident, treatment of skin infections, admission and stay in a home for the elderly). The indirect costs include the financial loss due to lower productivity and the loss of working hours, early retirement due to a disease. Along with a great financial burden, urinary incontinence may present also a severe personal stress. Urinary incontinence may also lead to cessation of sports activities. Physical inactivity has been identified as a risk factor for the development of several chronic non-infectious diseases. Originality: No such large-scale study on the prevalence of urinary incontinence among athletes has so far been conducted in Slovenia. The research findings, especially the identification of different risk groups of women, have an important implication also for the development of preventive and treatment measures of urinary incontinence in Slovenia Limitations of the study/further research: The difference in the number of women athletes engaged in specific sports was statistically significant, but some sports were, however, poorly represented. The prevalence and the type of urinary incontinence were identified only through a questionnaire. For more objective data, it would be necessary to perform also urodynamic investigations. Further research is recommended to explore the pelvic floor injuries which may occur during intensive training and the design of guidelines for preventive measures, especially the pelvic floor muscles exercises, in order to decrease the risks of this urological disorder among the targeted population.